1387. Phase I Study to Evaluate the Safety and Pharmacokinetics (PK) of Single and Multiple Ascending Doses (SAD/MAD) of Intravenous (IV) Minocycline in Healthy Adult Subjects. (26th November 2018) - Cornely, Oliver A; Arenz, Dorothee; Barraud, Olivier; Bayliss, Mark; Dimitriou, Vassiliki; Hamacher, Stefanie; Lovering, Andrew M; MacGowan, Alasdair; Cammarata, Sue K; Fusaro, Karen; Griffith, David C; Morgan, Elizabeth; et al.
Abstract: Background: Carbapenem-resistant Acinetobacter baumannii infections are defined by the WHO as a critical threat. IV minocycline is approved in the United States for treatment of Acinetobacter infections at doses up to 200 mg BID. This study investigated safety and PK of single and multiple doses of IV minocycline, including doses higher than approved in the United States. Methods: This was a randomized, double blind, placebo-controlled, SAD/MAD study of 6 doses (100–600 mg) of IV minocycline. Healthy adult subjects received a single dose of minocycline or placebo on Day 1, and 15 doses BID starting on Day 4. Safety was assessed throughout the study. Serial blood and urine samples were collected for PK assessment. Results: Sixty-nine healthy subjects were randomized, 49 were included in the PK analysis. No serious adverse events (AEs) occurred; 55 subjects (79.9%) reported study drug-related AEs; dizziness 40 (58.0%) and nausea 34 (49.3%) were the most common. All related AEs were mild except for seven subjects with moderate nausea and/or dizziness. Dosing in the 400 mg cohort was discontinued due to AEs, therefore MAD escalation was stopped. Subsequent cohorts were escalated for SAD and loading dose only. Conclusion: Single IV doses of minocycline up to 600 mg were tolerated reasonably well, but the maximum tolerated multi-dose was 300 mg BID. Most common AEs were mild nausea and dizziness with evidence of increasing incidence but not increasing severity with increasing dose. Exposure increased in a dose proportional fashion with exception of the 500 mg dose. The dosage regimen selected for further studies will be a 600 mg loading dose followed by 300 mg BID. Disclosures: O. A. Cornely, Innovative Medicines Initiative Joint Undertaking: Grant Investigator, Grant recipient. A. MacGowan, Merck: Commercial grant, Research support; Paratek: Commercial grant, Research support; VenatoRx: Commercial grant, Research support; Bayer: Commercial grant, Research support; Achaogen: Commercial grant, Research support; AiCuris: Collaborator and Commercial grant, Grant recipient and Research support; Polyphor: Commercial grant, Research support; Pfizer: Commercial grant, Research support; Roche: Commercial grant, Research support; Melinta: Industrial partner, Research support; MedImmune (AZ): Industrial partner (IMI), Research support; NIHR England: Grant Investigator, Grant recipient; MRC (UK): Grant Investigator, Grant recipient; Innovate UK: Grant Investigator, Grant recipient. Newton Fund (FCO): Grant Investigator, Grant recipient. S. K. Cammarata, Melinta Therapeutics, Inc.: Employee, Salary. K. Fusaro, Melinta Therapeutics: Employee, Salary. J. S. Loutit, The Medicines Company: Employee and Shareholder, Salary